Improvising "Nonexistent Rights": Immigrants, Ethnic Restaurants, and Corporeal Citizenship in Suburban California - Lee, Charles T. (Social Inclusion, 2019)
Building on Henri Lefebvre’s radical concept of "right to the city," contemporary literatures on urban citizenship critically shift the locus of citizenship from its juridical-political foundation in the sovereign state to the spatial politics of the urban inhabitants. However, while the political discourse of right to the city presents a vital vision for urban democracy in the shadow of neoliberal restructuring, its exclusive focus on democratic agency and practices can become disconnected from the everyday experiences of city life on the ground. In fact, in cities that lack longstanding/viable urban citizenship mechanisms that can deliver meaningful political participation, excluded subjects may bypass formal democratic channels to improvise their own inclusion, belonging, and rights in an informal space that the sovereign power does not recognize. Drawing on my fieldwork in the Asian restaurant industry in several multiethnic suburbs in Southern California, this article investigates how immigrant restaurant entrepreneurs, workers, and consumers engender a set of "nonexistent rights" through their everyday production and consumption of ethnic food. I name this improvisational political ensemble corporeal citizenship to describe the material, affective, and bodily dimensions of inclusion, belonging, and "rights" that immigrants actualize through their everyday participation in this suburban ethnic culinary commerce. For many immigrants operating in the global circuits of neoliberal capitalism, citizenship no longer just means what Hannah Arendt (1951) once suggested as "the right to have rights," or what Engin Isin and Peter Nyers (2014) reformulate as "the right to claim rights," but also the right to reinvent ways of claiming rights. I suggest such improvisation of nonexistent rights has surprising political implications for unorthodox ways of advancing democratic transformation.